1986
DOI: 10.1007/bf01648418
|View full text |Cite
|
Sign up to set email alerts
|

Fistula-in-ano is usually simple to manage surgically

Abstract: Our experience in the surgical management of 115 patients with fistula-in-ano treated over 14 years was reviewed retrospectively. The incidence of previous anorectal infection was 69%. After treatment eight patients (7%) developed a recurrence of the fistula and five (4%) experienced some complication directly resulting from surgical treatment. One patient died of pulmonary embolism following an operation for recurrence. Most of the patients (75%) had a successful outcome of a minor surgical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
0
6

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 2 publications
3
41
0
6
Order By: Relevance
“…Most fistulas in ano are easily managed by surgery alone 11 , although MRI is useful in complex cases. Lunniss et al 4 found that MRI could classify cryptoglandular fistula and also predict relapse with greater accuracy than EUA.…”
Section: Discussionmentioning
confidence: 99%
“…Most fistulas in ano are easily managed by surgery alone 11 , although MRI is useful in complex cases. Lunniss et al 4 found that MRI could classify cryptoglandular fistula and also predict relapse with greater accuracy than EUA.…”
Section: Discussionmentioning
confidence: 99%
“…A simple laying open procedure is effective for low or simple fistulas [26] . However, treatment of complex anal fistulas is challenging because internal and external sphincters are involved in the fistulous track and fecal continence could be impaired after surgery [27,28] .…”
Section: Discussionmentioning
confidence: 99%
“…Patients may also have systemic sepsis. There are many therapeutic options for anal fistula; however, fistulotomy, which involves division of all tissues encircled by the fistula, has a cure rate of over 90%, 3 and is the mainstay of treatment. There is nevertheless a risk of rendering the patient incontinent when the anal sphincter is divided.…”
mentioning
confidence: 99%